USING TEAM WORD-WEBBING TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION AT THE TENTH GRADE OF SMA USDATARA KOTA SORONG - Ahmad Wael (Qalam : Jurnal Ilmu Kependidikan, 2017)
This study was  carried  out  to  find  out  whether  or  not  team  word-webbing technique  can improve students’ reading comprehension on expository reading text comprehension, description text structure, particularly to the students at the tenth grade of SMA Usdatara Kota Sorong in academic year 2016/2017. In this study the writer used pre-experimental study. Pre-experiment or pre experimental, the design used in this study was the one group pretest-posttest design, the writer only teaches in one class because the school only has one class for each grade. This design includes a pre-test measure followed by a treatment and a post-test for a single group. From the statistical analysis by using paired sample t-test on SPSS 16.00, the output of statistical computation showed that the score of t-count was 6.749 with the df 18. The score of t-table for standard significant 5% (0.05) and df 18 was 2.101. Thus, the score of t count was higher than ttable (6.749 > 2.101), it can be clearly concluded that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that team word-webbing technique can improve students’ on reading expository text in comprehension description text structure, particularly to the students at the tenth grade of SMA Usdatara Kota Sorong in academic year 2016/2017.